Current and Forthcoming Issues in the South African Electricity Sector - Kessides, Ioannis N.; Bogetic, Zeljko; Maurer, Luiz (World Bank, Washington, DC, 2012)
One of the contentious issues in electricity reform is whether there are significant gains from restructuring systems that are moderately well run. South Africa's electricity system is a case in point. The sector's state-owned utility, Eskom, has been generating some of the lowest-priced electricity in the world, has largely achieved revenue adequacy, and has financed the bulk of the government's ambitious electrification program. Moreover, the key technical performance indicators of Eskom's generation plants have reached world-class levels. Yet the sector is confronted today with serious challenges. South Africa's electricity system is currently facing a tight demand/supply balance, and the distribution segment of the industry is in serious financial trouble. This paper provides a careful diagnostic assessment of the industry and identifies a range of policy and restructuring options to improve its performance. It suggests removing distribution from municipal control and privatizing it, calls for vertical and horizontal unbundling, and argues that the cost-benefit analysis of different structural options should focus on investment incentives and not just current operating efficiency.